Fučik Spectrum for the Second Order BVP with Nonlocal Boundary Condition - Sergejeva, N. (Nonlinear Analysis: Modelling and Control, 2007)
We construct the Fučik spectrum for some second order boundary value problem with nonlocal boundary condition. This spectrum differs essentially from the known Fučik spectra. We apply this result to the second order differential equation x’’ + g(x) = f(t, x, x’) with the conditions x(a) = 0, ∫ab x(s)ds = 0.